Service Recovery in Tourism: A Bibliometric-Based Systematic Review and Research Agenda - Tankus, Emre; Ozturk, Ilker; Mengus, Dogan Baran; Sokmen, Alptekin (Croatian Interdisciplinary Society, 2024)
Purpose: This study aims to eliminate the gap in this field by examining the concept of service recovery in the field of tourism with bibliometric technique. Design/methodology/approach: This study, data was obtained from the Web of Science database was used in the study. From this perspective, 247 articles in the field of tourism were included in the study and a systematic literature review of the articles was conducted. VOSviewer program was used to make bibliometric mapping of publications produced within the scope of this specific subject and discipline. Findings: Five clusters representing the research were identified. Additionally, the study identifies some gaps in the existing literature and provides a framework for future research. Expanding the digital, sustainability and legal dimensions of service recovery, better understanding the mechanisms, and examining recovery strategies as an investment are suggested as promising areas for future research. In this context, the study suggests guiding actions for researchers by identifying future research directions and the advantages it can provide to managers. Originality/value: The contribution of this article is to guide stakeholders who want to learn about this topic through the specific clusters created within the scope of co-citation relationships and the labels that represent them. It will also contribute to the emergence of new ideas that can guide researchers on service recovery.
Keywords: Social sciences (General); H1-99; bibliometric analysis; service recovery; tourism; Z31 [tourism JEL]